The evolution of radio sources from complete samples - Blundell, K; Rawlings, S; Willott, C; Lacy, M (1998)
From new complete samples of radio sources selected at low flux limits in low radio frequency, which give significantly improved coverage of the luminosity-redshift plane, we are able to decouple dependencies of source properties on redshift, from those depending on luminosity. We describe, with particular reference to the unification of radio galaxies and quasars, trends in linear size and also discuss core properties of these objects.